Analisis Pengaruh Tipologi Bentuk Bangunan terhadap Nilai Perpindahan Kalor pada Bangunan Kantor Sewa - Kurniashally, Nurul Qalbi; Alqadrie, Auliya Maula (Politeknik Negeri Pontianak, 2023)
Air conditioning is used to provide thermal comfort for building users is one of the conditions that often occurred in tropical buildings. As a result, the energy consumption of the building increased. One of the solutions to solve this problem is by reducing the heat that received by the building by finding the form of building. The process of determining the typology of office buildings is divided into 4 geometric form, namely squares, rectangles, triangles, and cylinders. The process is carried out with the function of the building as a rental office based on its geometric form. The method used is a simulation using the Ecotect program, for the weather data using Malaysia weather data which has been adjusted to the latitude of the location in Pontianak as well as some data obtained from BMKG for Pontianak City, West Kalimantan. In the process of simulating the shape of the building with the respect to the heat transfer value, several things are taken into consideration, namely the location, orientation, and the form of the building.